Preparation and photovoltaic properties of pyrene-thieno[3, 4-c]pyrrole-4, 6-dione-based donor-acceptor polymers. (December 2016) - Alqurashy, Bakhet A.; Iraqi, Ahmed; Zhang, Yiwei; Lidzey, David G.
Graphical abstract: Highlights: Four D-A copolymers were prepared and investigated for application in BHJ devices. Pyrene-alt-TPD polymers were prepared via direct arylation polymerisation method. Different substituents were attached to the polymer backbone. The synthesised polymers displayed high thermal stabilities. All polymers displayed modest efficiencies. Abstract: Four new donor-acceptor conjugated copolymers, containing pyrene moieties flanked by thienyl or bithienyl groups as a donor units and thieno[3, 4-c]pyrrole-4, 6-dione (TPD) as acceptor units, were successfully prepared via a direct arylation polymerisation method. While all polymers prepared had 2-ethylhexyloxy-substituents on the pyrene repeat units, two different alkyl-substituents (octyl or 4-hexylphenyl groups) were attached to their TPD moieties. The influence of these different substituents as well as the number of thienyl units linking the pyrene and TPD units along polymer chains on the photophysical, electronic and photovoltaic properties of these materials was investigated. All polymers displayed good thermal stability up to 315 °C. The optical band gap of the four polymers, PPEH DT-TPDO, PPEH DT-TPDHP, PPEH DT2-TPDO andPPEH DT2-TPDHP, were estimated to be 2.00, 2.06, 1.94 and 1.91 eV, respectively. Polymers that possessed a single thiophene unit attached to the pyrene unit, PPEH DT-TPDO andPPEH DT-TPDHP, displayed deeper HOMO levels compared to those with bithiophene units, PPEH DT2-TPDO andPPEH DT2-TPDHP . Photovoltaic devices were fabricated from all polymers.PPEH DT2-TPDO boasted the highest efficiency with a PCE (2.06%), a FF of 53.07%, a J sc of 4.66 mA/cm 2 and a V oc of 0.83 V.